1998
DOI: 10.1002/(sici)1096-9101(1998)22:5<302::aid-lsm7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periodontal pockets with a diode laser

Abstract: Background and Objective:The aim of this study is to examine the long-term effect of diode laser therapy on periodontal pockets with regard to its bactericidal abilities and the improvement of periodontal condition. Study Design/Materials and Methods: Fifty patients were randomly subdivided into two groups (laser-group and controlgroup) and microbiologic samples were collected. There have been six appointments for 6 months following an exact treatment scheme. After evaluating periodontal indices (bleeding on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
1
14

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(188 citation statements)
references
References 12 publications
9
164
1
14
Order By: Relevance
“…It has been reported that 2.5 W of diode laser irradiation could result in partial carbonizations of the root surfaces [22], but could achieve a bacterial reduction in periodontal pockets up to three log steps [23]. In another study, more than 50% of bacteria in the infected root canals could be killed by diode laser at a single irradiation with 2 W of laser power [13].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that 2.5 W of diode laser irradiation could result in partial carbonizations of the root surfaces [22], but could achieve a bacterial reduction in periodontal pockets up to three log steps [23]. In another study, more than 50% of bacteria in the infected root canals could be killed by diode laser at a single irradiation with 2 W of laser power [13].…”
Section: Discussionmentioning
confidence: 98%
“…Diode laser systems utilized in PDT may produce wavelengths which are absorbable by hemoglobin and would produce oxygenated hemoglobin and melanin; this phenomena happens when the wavelengths produced by laser systems belong to the infrared region (Moritz et al, 1998). Mechanism of action of low level laser therapy includes optical receivers' involvement in the electron transport chain on the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Diode lasers can be used for many soft tissue dental procedures, which include soft tissue surgeries [6][7][8] and periodontal [9,10] and peri-implant surgeries [11]. The study was carried out by using a diode laser for gingival retraction.…”
Section: Discussionmentioning
confidence: 99%